UV-response of aluminum-doped zinc oxide transparent films with different microstructures and electrical properties. (January 2021) - Villegas, E.A.; Ramajo, L.A.; Lere, M.E.; Castro, M.S.; Parra, R.
Abstract: Pure and aluminum doped-zinc oxide thin films were grown by spray-pyrolysis on glass substrates. The addition of increasing amounts of Al led to significant changes in the microstructure of the films. The texture coefficient of the (002) crystallographic plane was observed to decrease in heavily-doped films. Moreover, films with 10% at. Al showed a rare grain morphology characterized by worm-shaped grains. The presence of Al led to films of lower resistivity when compared to the pure-ZnO film, but the excess of doping agent had an opposed effect. This effect may be due to trap states in the form of ionized impurities and aluminum in interstitial sites. The electrical response of the films to UV light was evaluated, being the undoped films the ones showing the most intense response. The time needed for recovering the original current value after interrupting illumination was also measured and discussed. Highlights: The grain morphology in Al–ZnO thin films is highly dependent on the dopant content. Heavy Al doping (10% at.) changes grain morphology and crystalline orientation. The response of AZO films to UV-light depends on the Al content and generated defects.